2015
DOI: 10.1097/ajp.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Satisfaction as an Outcome Criterion in Research on Labor Analgesia

Abstract: A standard and validated tool to assess MS in clinical research on analgesia for labor is still to be developed. Power should be improved by acting on sample sizes or sensitivity of the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 133 publications
1
13
0
3
Order By: Relevance
“…Dans le contexte obstétrical, personnaliser l'analgésie du travail permettrait en sus d'éviter des excès d'analgésie, autre motif d'insatisfaction de la patiente. 3 On peut déjà prédire la douleur postopératoire/obstétricale ou les besoins en analgésie par la sensibilité préopératoire à une stimulation nociceptive standardisée, 4-8 mais de telles mesures sont difficiles à réaliser en pratique et ajoutent une épreuve douloureuse au patient. Le Pain Sensitivity Questionnaire (PSQ) explore la sensibilité naturelle d'un individu à la douleur au moyen de questions simulant des situations douloureuses plus ou moins intenses de la vie courante.…”
Section: Introductionunclassified
“…Dans le contexte obstétrical, personnaliser l'analgésie du travail permettrait en sus d'éviter des excès d'analgésie, autre motif d'insatisfaction de la patiente. 3 On peut déjà prédire la douleur postopératoire/obstétricale ou les besoins en analgésie par la sensibilité préopératoire à une stimulation nociceptive standardisée, 4-8 mais de telles mesures sont difficiles à réaliser en pratique et ajoutent une épreuve douloureuse au patient. Le Pain Sensitivity Questionnaire (PSQ) explore la sensibilité naturelle d'un individu à la douleur au moyen de questions simulant des situations douloureuses plus ou moins intenses de la vie courante.…”
Section: Introductionunclassified
“…This result is in accordance with previous studies reporting that BMI and maternal satisfaction with labor analgesia are inversely related. 12 Maternal obesity is also associated with poorer outcomes in epidural labor analgesia, such as more frequent difficulties in epidural catheter placement, epidural failure, and need for catheter replacement. 13,14 Moreover, maternal hypotension and fetal heart rate decelerations follow epidural analgesia during labor more frequently among obese than among nonobese parturients.…”
Section: Discussionmentioning
confidence: 99%
“…An association between impaired maternal satisfaction and greater cervical dilatation at admission has previously been reported, and the higher pain level at epidural placement might well be responsible. 12,20 When cervical dilatation occurs rapidly, a short duration of labor could explain the low analgesic effectiveness of the epidural technique. 21 We found that nationality was not associated with epidural analgesia effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…7 Among parturients who choose neuraxial procedures for labor, analgesic effectiveness is clearly an important component of maternal satisfaction. [3][4][5][8][9][10][11][12][13] However, the abolition of labor pain may be less important among parturients who decline readily available neuraxial analgesia in favor of nitrous oxide. 1,7 Nitrous oxide may provide nonanalgesic benefits that, for some parturients, supersede labor analgesic effectiveness in contributing to maternal satisfaction.…”
mentioning
confidence: 99%